Classification and Clinical Treatments for Unfavorable Fractures of the Proximal Segment in Sagittal Spilt Ramus Osteotomy: A Retrospective Study of 964 Cases. Issue 5 (7th July 2022) - Jiang, Nan; Wang, Min; Bi, Ruiye; Wu, Guomin; Zhu, Songsong
Abstract : Abstract: Unfavorable fractures in sagittal split ramus osteotomy are hard to manage. The aim of this study is to develop a new classification method for unfavorable fractures of the proximal segment to guide clinical managements. After reviewing 964 cases of sagittal split ramus osteotomy, we found that the unfavorable fractures can be divided into 3 types: mandibular ramus transverse fractures (Type 1), bad fractures accompanied by free fragments (Type 2), and unexpected separation patterns without free fragments (Type 3). We calculated the incidence of each fracture type and provided instructions for their corresponding treatments. Thirty-six patients suffered from unfavorable fractures (7.4% of patients), among which 32 patients had unilateral fractures and 4 patients had bilateral fractures. There were 2 Type 1 fractures (0.2% of split sites), 8 Type 2 fractures (0.8% of split sites), and twenty-six Type 3 fractures (2.3% of split sites). Type 1 unfavorable fractures are difficult to deal with, but Types 2 and 3 are generally manageable and they have no significant impact on the final outcomes. The new classification can effectively guide treatment strategies for unfavorable fractures. Severe cases of unfavorable fractures are rare, and most unfavorable fracture cases have a positive prognosis if correctly treated in time.